Object-Oriented Operating System Design and the Revival of Program Families - Schröder-Preikschat, Wolfgang; et al. (Proceedings of the Second International Workshop on Object Orientation in Operating Systems, 1991)
The `myth' is disproved that object-oriented operating systems offer pure performance in the area of distributed/parallel computing. Rather, it is true that the object-oriented paradigm is the only chance to build high-performance systems while maintaining a clean and evolutionary system structure.
UnivIS-Import:2015-04-16:Pub.1991.tech.IMMD.IMMD4.object_9